Non-invasive measurement of adrenocortical activity in Blue-fronted parrots (Amazona aestiva, Linnaeus, 1758) - Ferreira, João C. P. [UNESP]; Fujihara, Caroline J. [UNESP]; Fruhvald, Erika [UNESP]; Trevisol, Eduardo [UNESP]; Destro, Flavia C. [UNESP]; Teixeira, Carlos R. [UNESP]; Pantoja, José C. F. [UNESP]; Schmidt, Elizabeth M. S. [UNESP]; Palme, Rupert (Public Library of Science (PLoS), 2015)
Parrots kept in zoos and private households often develop psychological and behavioural disorders. Despite knowing that such disorders have a multifactorial aetiology and that chronic stress is involved, little is known about their development mainly due to a poor understanding of the parrots' physiology and the lack of validated methods to measure stress in these species. In birds, blood corticosterone concentrations provide information about adrenocortical activity. However, blood sampling techniques are difficult, highly invasive and inappropriate to investigate stressful situations and welfare conditions. Thus, a non-invasive method to measure steroid hormones is critically needed. Aiming to perform a physiological validation of a cortisone enzyme immunoassay (EIA) to measure glucocorticoid metabolites (GCM) in droppings of 24 Blue-fronted parrots (Amazona aestiva), two experiments were designed. During the experiments all droppings were collected at 3-h intervals. Initially, birds were sampled for 24 h (experiment 1) and one week later assigned to four different treatments (experiment 2): Control (undisturbed), Saline (0.2 mL of 0.9% NaCl IM), Dexamethasone (1 mg/kg IM) and Adrenocorticotropic hormone (ACTH; 25 IU IM). Treatments (always one week apart) were applied to all animals in a cross-over study design. A daily rhythm pattern in GCM excretion was detected but there were no sex differences (first experiment). Saline and dexamethasone treatments had no effect on GCM (not different from control concentrations). Following ACTH injection, GCM concentration increased about 13.1-fold (median) at the peak (after 3-9 h), and then dropped to pre-treatment concentrations. By a successful physiological validation, we demonstrated the suitability of the cortisone EIA to non-invasively monitor increased adrenocortical activity, and thus, stress in the Blue-fronted parrot. This method opens up new perspectives for investigating the connection between behavioural disorders and stress in this bird species, and could also help in their captive management.